Penurunan Prokrastinasi Akademik melalui Pelatihan Keterampilan Regulasi Emosi - Anniez Rachmawati Musslifah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
Procrastination in completing academic tasks is common to most students, including in the work of the thesis. One of the factors that cause students to delay completing the thesis is the ability to manage their emotions (emotion regulation). Karem training based on the theory of emotional regulation is expected to decrease the tendency of academic procrastination behavior in the students. This study aims to examine the effect of Karem training on academic procrastination in psychology faculty students of Muhammadiyah University of Surakarta. This study used Nonrandomized Control Group Pretest-Posttest experiment Design. The participants were final year students with a period of more than 10 semesters or 5 years and has taken a thesis course more than 2 semesters or 1 year. The results of this study indicate that Karem training has a significant effect on the decrease of procrastination in the final grade students who are completing the thesis.